Does Education Matter for Income Inequality? Evidence from Sub-Saharan Africa - Panton-Ntshona, Sherine (Graduate School of Business (GSB), 2022)
The issue of income equality has become of great concern on a global scale. Since the 2008 global financial crisis, economists and other socioeconomic analysts have observed the state of the income and wealth gap between the top ten percent rich and the lower forty percent poor of populations, and its far-reaching impact on the lives of ordinary people. Income inequality has become a global challenge and the effects are felt in both developed and developing countries. The socioeconomic disparity between the rich and poor is pronounced in developing countries, and recent trends of growing inequality are being observed in developed countries. This research examines the effect of education on income inequality and GDP per capita, using a panel dataset of 18 selected sub-Saharan countries for the period from 1994 to 2015. The panel models are estimated, using the fixed effects, random effects and generalised methods of moments estimation techniques. The results show that the relationship of education and its impact on income inequality is dependent on the level of education being assessed. High resource input in tertiary education increases income inequality, while high resource input in lower educational levels reduces income inequality. Overall, increases in government expenditure on education lead to increase in inequality and a fall in GDP per capita. These results show possible inefficiencies in the allocation of educational resources in sub-Saharan countries during the period of investigation. Government spending on education does not reduce inequality or boost income unless it is done efficiently. To reduce income inequality and increase average income, educational resources must be efficiently allocated with priority given to the educational levels of the highest proportions of the population.